The effect of BCG vaccination and risk factors for latent tuberculosis infection among college freshmen in China. (September 2022) - Huang, Wei; Fang, Zhixiong; Luo, Si; Lin, Sha; Xu, Lei; Yan, Bo; yang, Yang; Liu, Xuhui; Xia, Lu; Fan, Xiaoyong; Lu, Shuihua
Highlights: Bacillus Calmette–Guérin (BCG) vaccination can reduce the infection rate of Mycobacterium tuberculosis (MTB). The protective effect of BCG can be maintained until college enrollment. The ESAT6-CFP10 skin test (ECST) may underestimate the protective effects of BCG. The protective effect of BCG is better among college freshmen from rural areas. Abstract: Objectives: In this study, we aimed to verify whether Bacillus Calmette–Guérin (BCG) can protect first-year college students against Mycobacterium tuberculosis (MTB) infection by the recombinant fusion protein ESAT6-CFP10 skin test (ECST) or the tuberculin skin test (TST). Methods: We conducted a cross-sectional study to assess risk factors for latent tuberculosis infection (LTBI). Vaccine effectiveness of BCG against LTBI, measured by ECST and TST separately, was assessed using multivariable logistic regression. Results: A total of 7351 college freshmen accepted ECST, whereas 7228 accepted TST. A total of 263 (3.58%) tested positive with ECST and 581 (8.04%) tested positive with TST. BCG was significantly associated with LTBI (ECST: adjusted odds ratio (aOR) = 0.26; 95% CI 0.09 to 0.73; TST: aOR = 0.25; 95% CI 0.13 to 0.49). The BCG protective effect on freshmen living in rural areas (ECST: aOR = 0.16; 95% CI 0.04 to 0.55; TST: aOR = 0.12; 95% CI 0.04 to 0.33) is better than that of freshmen living in cities (ECST: aOR = 0.53; 95% CI 0.07 to 4.03; TST: aOR = 0.44; 95% CI 0.17 to 1.16). Conclusions: Protection against LTBI was strongly associated with BCG vaccination. A novel skin test (ECST) may underestimate the protective effects of BCG in college freshmen. BCG has better protection in areas with a slightly higher incidence of LTBI.